2017
DOI: 10.1186/s12913-017-2472-0
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation costs of metastatic melanoma in France; the MELISSA study (MELanoma In hoSpital coSts Assessment)

Abstract: BackgroundManagement of metastatic melanoma is changing rapidly following the introduction of innovative effective therapies, with consequences for the allocation of healthcare resources. The objective of this study was to assess hospitalisation costs of metastatic melanoma in France from 2011 to 2013 from the perspective of the government payer.MethodsThe population studied corresponded to all adults with metastatic melanoma hospitalised in France between 1st January 2011 and 31st December 2013 who required c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…current 2019 U.S. dollars, is roughly $5,720. 35 This estimate falls within the range of annualized PPPM costs associated with hospitalizations reported in this study across first-line treatment groups ($4,452-$12,798). Additional studies in the United States assessing costs of care for metastatic melanoma that consider contemporary, recently approved systemic therapies are needed to make further comparisons to the results of the current study.…”
supporting
confidence: 67%
“…current 2019 U.S. dollars, is roughly $5,720. 35 This estimate falls within the range of annualized PPPM costs associated with hospitalizations reported in this study across first-line treatment groups ($4,452-$12,798). Additional studies in the United States assessing costs of care for metastatic melanoma that consider contemporary, recently approved systemic therapies are needed to make further comparisons to the results of the current study.…”
supporting
confidence: 67%
“…Generally, melanoma progression and changes in prognosis impact the use and allocation of healthcare resources and the economic burden [ 33 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that hospitalization costs related to melanoma increase approximately fourfold with disease progression; new therapies may delay the risk of relapse, but the acquisition cost and, in certain cases, their long-term use or drug toxicity increase the cost of melanoma care [ 9 , 42 , 44 , 45 ]. More recently, it has been observed that MM patients treated with at least one dose of the anti-CTLA-4 inhibitor ipilimumab need various types of healthcare services and that the economic burden associated with a drug-refractory disease is high.…”
Section: Discussionmentioning
confidence: 99%
“…The largest cost drivers in France, Germany and the United Kingdom are medications and hospitalisation and/or emergency department treatment [ 127 ]. Adverse events from the use of new treatments are also responsible for a sizable cost burden [ 128 , 129 ].…”
Section: Harms Of Exposure To Uv Radiationmentioning
confidence: 99%